Jejak Habaib dalam Manuskrip Borneo (Melacak Peran Ulama dalam Penanaman Nilai Pendidikan Multikultural) - Iskandar Iskandar; Maisyarah Rahmi Hasan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The presence of habaib in Nusantara and Kalimantan (Borneo) not only leaves a historical trace, but also leaves an important role in instilling the value of multicultural education for the community. The traces and role of this habaib are depicted in several manuscripts of handwritten works left by the Kutai Kartanegara sultanate and Pontianak Sultanate that had triumphed in their time. The famous Kutai Kartanegara sultanate manuscripts are Salasila Kutai, Panji Salatin and Baraja Niti. While the famous Pontianak Sultanate manuscripts are Prince Sharif's Syair Script and Bahar Al-Lahut's Script. This research wants to answer the question of how habaib traces in Borneo manuscripts? and what are the roles of habaib as a cleric in the multcultural education of the people of the Sultanate of East Kalimantan and West Kalimantan? The manuscripts of the sultanate were then traced according to a philological approach and analyzed with a historical and paedagogic approach. The results of the analysis illustrate that habaib as a scholar has a role in instilling the value of multicultural education. The habaibs serve as preachers, teachers, and muftis, as well as sulthans in the system of government.